Characteristics of women with chronic pelvic pain referred to physiotherapy treatment after multidisciplinary assessment: a cross-sectional study - Nygaard, Ane Sigrid; Stedenfeldt, Mona; Øian, Pål; Haugstad, Gro Killi (Scandinavian Journal of Pain, 2019)
Accepted manuscript version, licensed CC BY-NC-ND 4.0. Background and aims - Chronic pelvic pain (CPP) in women is a complex condition that can seriously impact health and quality of life. Clinical guidelines for CPP place great demands on healthcare professionals, as they require both specialized knowledge about the pelvic area and knowledge of the mechanisms of chronic pain. To ensure best possible assessment and treatment of these women it is important to bring about more knowledge of the special CPP features. The purpose of this paper is to describe the characteristics of women with CPP evaluated at the University Hospital of North Norway, and further referred to physiotherapy. The frequency of having a history of abuse or previous pelvic surgery will also be reported, and analyses performed to investigate if subjective health status differs between women with and without these experiences. Methods - We collected cross-sectional data from 62 women with CPP aged 20–65 (mean age 38.0), referred to physiotherapy after assessment by medical specialists. Data were collected by semi-structured interviews for demographic variables and medical history, and self-administered questionnaires on pain intensity, sexual function, urinary incontinence (UI), anal incontinence (AI), obstructed defecation syndrome (ODS), subjective health complaints (SHC) and symptoms of anxiety and depression. Results - Pain duration of more than 10 years was reported by 42%, mean pain score was 4.7/10, and analgesics were used weekly by 48%. Previous pelvic or abdominal surgery was reported by 71%, and sick leave >12 weeks the last year by 34%. Reduced sexual desire was reported by 78%, dyspareunia by 73%, UI by 54%, AI by 23%, and obstructed defecation syndrome (ODS) by 34%. More than 90% reported musculoskeletal or pseudoneurologic complaints. Anxiety and depression scores defined as requiring treatment were reported by 40%. Abuse was reported by 50%, and associated with significantly more reports of ODS ( p =0.02), more SHC ( p ...